Seismic analysis of Fujian Hakka Tulous - Bruno Briseghella (2019)
The overall earthquake response of Hakka Tulous, traditional earth constructions of the Fujian Province (China) and listed among the UNESCO World Heritage buildings, is investigated. Non-linear static analysis (pushover) with the equivalent frame approach is used. Although some rough approximations are assumed, this approach is well suited to model complex masonry structures, like Tulous. In fact, nonlinear analysis implemented by finite elements or by discrete elements would involve complex models hard to converge and needing long computational time. After carrying out seismic analysis of a Tulou prototype, its failure modes and overall seismic response were evaluated. The Tulou has shown to have good earthquake resistance with respect to the maximum seismic action that can be expected in the Fujian Province.